Distribution of infertility factors among infertile couples in Yemen - Allow, Ahmed Kaid Naji; Abdulmogny A, Sadek S. M.; Bracamonte, Maryam; Kaid, Belqees (Journal of Clinical Developmental Biology, 2016)
Background: Infertility is a global health issue and determines as a one of the most prevalent health disorders among young adult couples. It is well known that 50-80 million people are facing the problem of getting an integrated family. In the last thirty years the causes of infertility are varied from one population to another. Objectives: To evaluate the distribution of infertility causes in patients attending Allow In Vitro Fertilization (IVF) center for infertility treatment. Patients and methods: This study is a retrospective study. Data of 2622 infertile couplesfor a 5 years(fromSeptember 2007 to September 2012) period was derived from Allow IVF center. Results: the male factor infertility was 29.90% (1281/2622) was common versus female factor of infertility which was 24.37%. The combined infertility has been found in 34.25% of population. The isolated tubal infertility factor was documented in 3.70% (97/2622). The rate of unexplained infertility was observed in 11.48% of the population. Conclusion: In summary, male factor infertility and anovulation, in the last thirty years, are still the driving causes of infertility problem in our population. The seminal fluid infection and sperm agglutination were the common male infertility subdivision causes in separate and combined infertility.